Fiscal pedal : fraud or creative accounting? : a theoretical understanding of the dangerous fiscal cycles that affected the Brazilian economy - Arraes, Jeremias Pereira da Silva (2023)
This essay aims to discuss, in a theoretical way, how creative accounting is presented in Brazil in the years 2014 and 2015, which resulted in an impeachment process and affected the Brazilian economy. The methodology is qualitative with the application of content and document analysis techniques. The basis of the accounting information is taken from the analyzes of the special impeachment commission and the Federal Court of Auditors in relation to the accusation of a crime of fiscal responsibility to the detriment of the president of the republic. The research discusses the accounting operations carried out by the government and which resulted in the famous expression “fiscal pedaling”. In light of accounting theory Hendriksen and Van Breda (2018), there is a complexity in the analysis that has led to frequent divergences regarding the objectives of accounting and the nature of the economic environment in which it operates. Thus, as research results, it is possible to observe that the concepts given to creative accounting and fraud are close, but they are not similar, where characteristics such as intentional error and the transit of accounting operations, outside the accounting regulations and principles, end up elucidating the particularities of each phenomenon.